DOP03 Unfermented β-fructan fibres can induce gut inflammation and tumorigenesis in select Inflammatory Bowel Disease patients mediated by gut microbiota. (30th January 2023) - Voisin, A; Mahmood, R; Jeanson, T L; Bernstein, C; Armstrong, H; ,
Abstract: Background: Dietary fibres are not digested in the bowel; they are fermented by microbes, typically promoting gut health. However, IBD patients have altered gut microbiota composition and can experience sensitivity to consumption of fibres. Our previous findings offered the first mechanistic evidence that if dietary β-fructans (inulin and oligofructose) are not fermented by gut microbes in IBD patients, these fibres can induce inflammation. This diet-induced inflammation could have serious repercussions as chronic inflammation creates a mutagenic environment that promotes progression to colorectal cancer (CRC). We hypothesized that unfermented β-fructans cause tumorigenesis and promotion of IBD progression to CRC. Methods: We examined pathways associated with response to β-fructan in a randomized controlled trial examining β-fructan supplementation (15g/day) in UC patients in remission (RNA sequencing). We validated pathways of interest in IBD patient colonic biopsies cultured ex vivo with β-fructans (targeted proteomics and mesoscale discovery). We examined structural changes (microscopy; e.g., tumorigenic architecture) in these biopsies. Further, cell invasion, migration, and proliferation were examined using scratch wound assays and chick chorioallantoic membrane assays (CAM; n=10 embryos per treatment). Results: CRC-related pathways (SLIT2/MAPK and SOS1) were induced and anti-tumour gene RPS27A was reduced only in biopsies from remission UC patients who entered relapse following consumption of β-fructans (endpoint versus baseline), not those in the placebo arm who relapsed. Pathways were validated in IBD patient colonic biopsies cultured ex vivo demonstrating oligofructose produced more significant effects than inulin; response correlated with disease severity. Inulin and oligofructose further influenced the processes of migration and invasion reflective of the tumorigenic process of epithelial to mesenchymal transition and risk of CRC. Conclusion: Our findings suggest that intolerance and avoidance of fibres in select IBD patients occurs specifically in patients whose gut microbiota do not support fermentation of dietary fibres resulting in increased presence of unfermented dietary fibres in the gut. Here we show that these β-fructan fibres commonly touted as beneficial prebiotics can elicit gut inflammation and tumorigenesis in this subset of IBD patients, suggesting consumption of these fibres should be avoided in these patients.